Synergistic effect of Maquiberry cystatin, sodium fluoride and stannous chloride for the prevention of initial dental erosion in vitro - Vinícius Taioqui PELÁ; Thelma Lopes SILVA; Even Akemi TAIRA; Geórgia Almeida SANT’ANA; Letícia Oba SAKAE; Flávia Mauad LEVY; Taís Scaramucci FORLIN; Eduardo Pereira de SOUZA; Talita Mendes Oliveira VENTURA; Thiago Saads CARVALHO; Adrian LUSSI; Marília Afonso Rabelo BUZALAF (Journal of Applied Oral Science)
Abstract Objective This study analyzed the synergistic effect between a recombinant Maquiberry (MaquiCPI-3) protein, sodium fluoride (NaF), and stannous chloride (SnCl2) against initial dental erosion in vitro. Methodology A total of 98 bovine enamel samples were prepared and allocated to seven treatment groups (n=14/group) as follows: deionized water (Water); commercial solution, 800 ppm Sn+2, 500 ppm F-, ElmexTM, Erosion, GABA, Therwil, BL, CH (Elmex); 500 ppm of fluoride (F-) from NaF (NaF); 500 ppm of F- from NaF and 800 ppm of tin (Sn+2) from SnCl2 (NaF+SnCl); 0.5 mg/mL MaquiCPI-3 (MaquiCPI-3); combination of MaquiCPI-3 and NaF (Maqui+NaF) and; combination of MaquiCPI-3, NaF and SnCl (Maqui+NaF+SnCl). Samples were treated with the respective solutions (250 μl, 2 min, 37°C, 250 rpm). After forming the acquired enamel pellicle (AEP) by adding human saliva from nine volunteers (250 μl, 1 h, 37°C, 250 rpm), the samples underwent acid challenge (1 mL, 1% citric acid, pH 3.6, 1 min, 25°C, 250 rpm). All procedures were performed in triplicate. Surface microhardness change percentage (%SMC) and relative surface reflection intensity (%SRI) were measured and analyzed by One-way ANOVA/Tukey’s tests (p<0.05). Results The Elmex, NaF, NaF+SnCl, MaquiCPI-3, Maqui+NaF, and Maqui+NaF+SnCl groups showed significantly lower %SMC compared with Water. The NaF, Sn+2, NaF+SnCl, MaquiCPI-3, Maqui+NaF and Maqui+NaF+SnCl groups exhibited significantly greater protection compared with Elmex. Maqui+NaF+SnCl revealed better enamel protection (significant) when compared with the MaquiCPI-3 and Maqui+NaF groups. Elmex, NaF+SnCl, MaquiCPI-3, Maqui+NaF, and Maqui+NaF+SnCl had a significantly higher %SRI compared to the Water and NaF groups, which did not differ between each other. Conclusion All treatment solutions provided protection against initial dental erosion in vitro. Formulations containing Maqui+NaF+SnCl2 offered superior enamel protection compared with MaquiCPI-3 alone.